2022
DOI: 10.1136/bmjopen-2022-061873
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality for abstracts of randomised trials on child and adolescent depression prevention: a meta-epidemiological study on adherence to CONSORT for abstracts

Abstract: ObjectivesThis study aimed to investigate adherence to Consolidated Standards of Reporting Trials (CONSORT) for abstracts in reports of randomised trials on child and adolescent depression prevention. Secondary objective was to examine factors associated with overall reporting quality.DesignMeta-epidemiological study.Data sourcesWe searched MEDLINE, EMBASE, PsycINFO, PsycArticles and CENTRAL.Eligibility criteriaTrials were eligible if the sample consisted of children and adolescents under 18 years with or with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…Fundytus et al showed that the vast majority of oncology randomized controlled trials are now funded by industry-they are larger, more likely to be positive, and published in higher impact journals than trials without industry support [31]. Furthermore, the results of a study by Wiehn et al showed that adequate reporting varied considerably across CONSORT items with information on blinding and adverse effects being the least reported [32]. Although the results of several studies have concluded that funding is mostly not included in the abstract of randomized controlled trials, it has been observed that funding is reported in the full text of the randomized controlled trial articles.…”
Section: Discussionmentioning
confidence: 99%
“…Fundytus et al showed that the vast majority of oncology randomized controlled trials are now funded by industry-they are larger, more likely to be positive, and published in higher impact journals than trials without industry support [31]. Furthermore, the results of a study by Wiehn et al showed that adequate reporting varied considerably across CONSORT items with information on blinding and adverse effects being the least reported [32]. Although the results of several studies have concluded that funding is mostly not included in the abstract of randomized controlled trials, it has been observed that funding is reported in the full text of the randomized controlled trial articles.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors were also included as potential predictors of the abstracts' reporting quality. The variables included in the analysis were as follows: study sample size (number of included participants <100 or ≥100), journals' impact factor and quartile, number of authors, type of abstract (structured or non-structured), presence of a recommendation for the use of CONSORT statement in the journal's instructions for authors, number of clinical centers (single or multi-centric study), statistical significance of the results (favoring experimental or control treatment), hospital setting, and funding by industry [23][24][25]33]. To determine the journals' impact factor and quartile, data from the Thomson Reuters Journal Citation Report for 2022 were utilized and included as variables in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For health professionals, abstracts serve as a primary source of information about a trial, influencing their decision-making in patient management. In many cases, due to time constraints or limited access to full texts, practitioners rely solely on abstracts to make treatment decisions, making the quality of abstract reporting paramount [23,24]. Furthermore, researchers conducting systematic reviews and meta-analyses rely on abstracts to identify eligible studies, and poor reporting can lead to the exclusion of relevant research, potentially distorting evidence synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations